Factors predicting financial well-being of government employees in selected states in Malaysia - Fazan Ahmad, Noor Diyana (2014)
Financial well-being is an important aspect of overall well-being as it determines how financially stable or satisfied a working individual is in their current situation. There are many factors that can predict the likelihood of a high level of financial well-being and several of the factors based on past research were focused in this study. These factors consist of the resources available currently and how it will be implemented to predict either a high or low level of financial well-being. Thus, the aim of this study is to determine the strongest predictor of government employees‟ financial well-being. Among the factors are socio-economic factors such as income level, gender, age, education level and strata as well as financial problems, locus of control and dimensions of financial management practices which includes cash-flow, savings, credit management and risk management. To determine the sampling areas, the multi-stage random sampling method is used and the states selected were Pahang, Kelantan, Johor, Melaka and Negeri Sembilan. Each state was categorized into urban and rural areas. Lists of government departments were obtained for each urban and rural area of the selected states departments in the second stage of sampling. Before the distribution of the questionnaires, permissions were obtained from the selected departments and a total of 472 usable questionnaires were collected. Statistical Package for Social Sciences (SPSS) was used to analyse the data for this research and the tests used were Pearson Correlation, t-Test analysis, Chi-Square Analysis and Logistic Regression analysis. Results from this study showed that the most significant factor in predicting the likelihood of high level of financial wellbeing was credit management. Following this, the other significant predictors of financial well-being were income, locus of control, education and financial problems. Therefore, several steps should be taken by the government, educators, relevant agencies and government employees to ensure a higher level of financial well-being. Steps that should be taken such as providing opportunities for government employees to increase their income and encourage good financial management practice. Financial management practices especially in terms of credit management from an early age through education should be encouraged, to ensure a high level of financial well-being among government employees in Malaysia.